USE THE ATTENDANCE SYSTEM AND ITS RELATION BARCODE READER IN ATTENDANCE AT PT.BLUEBIRD ALLOWANCES - Supriatna Supriatna; Drs.Soenarto Usna (Jurnal Sistem Informasi, 1998)
Use the computer as a tool in the attendance at PT.BLUE BIRD felt very usefulwhere previously was done manually, are now no longer so in the process ofdelivering information can be more accurate and faster. And using the computer canbe minimized fraud by employees who have often encountered in the attendancesystem using machine Amano. And the results to objects of a reliable data